The Effect of Work Motivation an Pengaruh Motivasi Kerja Dan Sikap Kerja Terhadap Kinerja Karyawan (Studi Kasus Pada Karyawan PT. Mitra Karya Banten) - Shoma Febriyani; Indina Dhesta Nugrahaeni; Palahiyah Palahiyah (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2022)
This study aimed at revealing the Work Motivation and Work Behavior towards Employees’ Work Performance. This study used a quantitative method with questionnaire and survey as the instrument. The data of 57 employees in PT. Mitra Karya Banten were collected by using Probability Sampling method which is random selection method that is used slovin formula. The data was examined by using classical assumption test, double linear regression analysis, t-test, f-test using the application of SPSS 20th version. The results show that: (1) work motivation have the positive effect and is important for the employees’ work performance, based on result of output result show tcount > ttable (2,383 > 1,673), and have value (0,021 < 0,05). (2) work behavior have the positive effect and is important for the employees’ work performance, based on result of output result show tcount > ttable (3,063 > 1,673), and have value (0,003 < 0,05). Keywords: Work Motivation, Work Behavior, Employees’ Work Performance.